EFEKTIVITAS INTENSITAS NAUNGAN DAN POC AIR KELAPA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascolonicum L.) - Ariska, Nana; Taufiq, Taufiq; Putra, Iwandikasyah; Latief, Abdul (Agros Journal of Agriculture Science, 2024)
Shallots (Allium ascalonicum L.) are one of the main vegetable commodities that have many benefits. Shallot supply has not kept up with the rising demand; low production is a result of an underutilized agricultural system. Light and overuse of inorganic fertilizers are two examples of external or environmental elements that have an impact on the agriculture system. This study's experimental design, which is a Randomized Group Design (RGD) factorial pattern with three replications in a 3X3 matrix, was the research methodology. The findings demonstrated that all parameters of shallot plant development and production examined did not exhibit any relationship between the severity of shade and the interval of coconut water LOF application. This suggests that shallot plant development and production are not considerably impacted by the shade intensity and coconut water LOF interval combination. The height of shallot plants at 15, 30, and 45 DAP is not significantly affected by the coconut water LOF irrigation interval. The coconut water LOF watering intervals of once per day (I1) and once every three days (I2) were determined to be the most effective treatments. Regarding every aspect of shallot plant development and production, there is no correlation between the interval of coconut water POC and the amount of shadowing. Key-words: shallot, allium ascalonicum, vegetable.